Über die Approximation von analytischen Funktionen durch algebraische Polynome - Naftalewitsch, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Г. Нафталевич. О приближении аналитических функций алгебраическими многочленамиA. Naftalevičius. Apie tolydinių funkcijų aproksimavimą polinomais